The few and the many: A motif of Augustine"s controversy with the Manichaeans - Hoffmann, Andreas (HTS teologiese studies, 2013)
It is one fundamental conviction of ancient philosophy that, in contrast to the vast majority, only few are able to gain knowledge of truth. This axiom, which also underlies Cicero’s Hortensius, is adapted by the young Augustine. When looking for a concept of truth that combines the ideal of a philosophical existence with Christianity, he decides to join the Manichaeans. As opposed to the ‘mainline church’ of the catholica in which ‘the many’ are gathered, the Manichaeans appear to him as a small, elitist Christian community meeting higher intellectual as well as ethical demands. This claim seems to be particularly and impressively confirmed by the ‘pauci electi’. Their approach has apparently strengthened Augustine’s belief that true, higher Christianity is to be found amongst the Manichaeans. When he later devotes himself to the catholica and leads the fight against the Manichaeans, Augustine adheres to the conviction of the ‘few wise’. Also within the catholica only few attain maximum insight and lead an appropriate life. At the same time, however, Augustine increasingly considers ‘the many’ as positive. These two aspects are combined in his epistemological concept of ‘auctoritas’: by means of their auctoritas, the few ‘wise’ within the Catholic Church are supposed to guide the many towards truth on their journey of faith and cause them to improve their moral conduct. Its big success is a major argument for the catholica, whilst the ‘paucitas’ of the Manichaeans (and all heretics) can be considered evidence of the groundlessness and absurdity of their doctrine.